2019
DOI: 10.3389/fphar.2019.00195
|View full text |Cite|
|
Sign up to set email alerts
|

Resveratrol Ameliorates Glucocorticoid-Induced Bone Damage in a Zebrafish Model

Abstract: Resveratrol (Res) is a multi-functional polyphenol compound that has protective functions in cardiovascular and neurodegenerative diseases. This study aimed to determine the effect of Res on osteogenic differentiation and bone mineralization in zebrafish ( Danio rerio ) with dexamethasone (Dex)-induced bone damage. Our results showed that Dex exposure (15 μmol/l) decreased the green fluorescence areas and the integrated optic density (IOD) values in the skull bones of zebrafish larvae of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…ALP activity and mineralization are respectively recognized as the early and late markers of osteogenic differentiation in osteoblast. ALP is generated by osteoblasts and conveyed to the extracellular matrix, resulting in the generation of hydroxyapatite, which implies that osteogenic differentiation is initiated in the first stage (Liu et al, 2019; Ozeki et al, 2008; Xie et al, 2019). In the second stage, mineralization occurred in the extracellular matrix and united to calcium nodules (Wang, Olson, Cheng, Guo, & Wang, 2012), which is known as a mark of osteoblast differentiation and maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALP activity and mineralization are respectively recognized as the early and late markers of osteogenic differentiation in osteoblast. ALP is generated by osteoblasts and conveyed to the extracellular matrix, resulting in the generation of hydroxyapatite, which implies that osteogenic differentiation is initiated in the first stage (Liu et al, 2019; Ozeki et al, 2008; Xie et al, 2019). In the second stage, mineralization occurred in the extracellular matrix and united to calcium nodules (Wang, Olson, Cheng, Guo, & Wang, 2012), which is known as a mark of osteoblast differentiation and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Both larval and adult zebrafish were applied for various developmental ages but the unique superiority exists at larval zebrafish since it is appropriate to be applied in multi‐well plate screening assays. Primary organs and tissue structure are sufficiently developed at the stage of zebrafish larvae, and it has become an ideal model for bone research (Barros, Alderton, Reynolds, Roach, & Berghmans, 2008; Geurtzen et al, 2017; Luo et al, 2016, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (trans-3,4′,5-trihydroxystilbene, RSV) is a natural polyphenolic phytoalexin present in several plant species, such as peanuts, grapes, and herbs [ 4 ]. Mounting evidence has demonstrated the potential chemopreventive and chemotherapeutic activities of resveratrol in multiple diseases, including cancer, diabetes, cardiovascular disease, neurodegenerative disease, and metabolic disease [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Barrett and colleagues demonstrated that tissue ossification was reduced in zebrafish larvae exposed to prednisolone and that phenotype could be partially rescued upon treatment with bisphosphonates (Barrett et al, 2006), a key similarity to human GIOP (Hayat and Magrey, 2020). Still in zebrafish larvae, resveratrol was shown to counteract the OP phenotype induced by dexamethasone (Luo et al, 2019), as described for mammals (Tou, 2015). Further studies aiming at validating the suitability of the fish model have evidenced an effect of prednisolone on bone homeostasis, through the altered expression of genes (i) involved in osteoblast (entpd5a) and osteoclast (acp5a and sost) differentiation, (ii) crucial to extracellular matrix (ECM) mineralization (mmp9 and mmp13), and (iii) involved in pathways critical to osteoblast and osteoclast signaling (Huo et al, 2018).…”
Section: Glucocorticoid Induced Osteoporosismentioning
confidence: 99%